Quality of service at the geriatric outpatient department of a social security hospital: A qualitative study - Apaza-Pino, Rossana (2018)
Objective: To determine the quality of service to elderly patients in geriatric outpatient levels of care. Materials and methods: A qualitative study with a group of 45 participants over 60 years of age who attended the geriatric department of the Hospital Guillermo Almenara Irigoyen between January and June 2005. Results: It was determined that 77 % of the participants were satisfied with the quality of care. The categories with the greatest complaints were lack of patient-physician interaction, lack of empathy, and lack of safety during their health care. Aspects that stood out were reliability and information submission. Conclusions: The lack of patient-physician interaction and lack of empathy are the most outstanding problems in the geriatric department.